Hierarchically porous N-doped carbon nanosheets with atomically dispersed Fe/Co dual-metallic sites for efficient and robust oxygen electrocatalysis in Zn–air batteries. (31st August 2022) - Liu, Zheng-Qi; Ma, Fei-Xiang; Xiong, Yu-Xuan; Zhang, Meng-Tian; Du, Yue; Zhen, Liang; Xu, Cheng-Yan
Abstract : Dual-metallic Fe/Co/N co-doped porous carbon nanosheets (Fe/Co–N–C NSs) with hierarchical porous structures and abundant exposed bimetallic Fe/Co–N x active sites can be utilized as efficient ORR electrocatalysts. Abstract : The design and synthesis of non-precious-metal single-atom catalysts with favorable coordination environments and abundant accessible active sites to boost the sluggish oxygen reduction reaction (ORR) is highly desirable for both fuel cells and metal–air batteries. In this work, atomic Fe/Co dual sites anchored on N-doped carbon nanosheets (Fe/Co–N–C NSs) with thickness below 8 nm are fabricated via a polyvinylpyrrolidone-directed chemical blowing strategy together with a subsequent pickling step and metal atom trapping. Detailed characterizations including atomic-resolved HAADF-STEM observation and BET analysis revealed that the dual-metallic Co/Fe–N x moieties are uniformly dispersed in highly porous Fe/Co–N–C NSs with abundant hierarchical pores below 4 nm. Thanks to the synergic effect of dual-metallic Fe/Co–N x active sites and abundant accessible catalytic sites provided from the hierarchically porous nanosheet structures, the resultant Fe/Co–N–C NSs delivered excellent ORR performance in 0.1 M KOH with a positive half-wave potential ( E 1/2 ) of 0.88 V vs. RHE, high kinetic current density ( J k ) of 24.8 mA cm −2 at 0.85 V and robust stability, exceeding those of commercial Pt/C and mono-metallic Fe–N–C NSs. When Fe/Co–N–C NSs were employed as air cathode catalysts for primary Zn–air batteries, the assembled cells delivered an open-circuit voltage up to 1.52 V and a peak power density of 165 mW cm −2 .